2013
DOI: 10.1038/nsmb.2521
|View full text |Cite
|
Sign up to set email alerts
|

Macrodomain-containing proteins are new mono-ADP-ribosylhydrolases

Abstract: ADP-ribosylation is an important post-translational protein modification (PTM) that regulates diverse biological processes. ADP-ribosyltransferase diphtheria toxin-like 10 (ARTD10, also known as PARP10) mono-ADP-ribosylates acidic side chains and is one of eighteen ADP-ribosyltransferases that catalyze mono- or poly-ADP-ribosylation of target proteins. Currently, no enzyme is known that reverses ARTD10-catalyzed mono-ADP-ribosylation. Here we report that ARTD10-modified targets are substrates for the macrodoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
373
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(387 citation statements)
references
References 51 publications
10
373
4
Order By: Relevance
“…1, C and D), indicating that, at least for murine innate cells, PARP12 is a genuine interferon stimulated gene or ISG. Finally, the capacity of PARP12 to express ADP-ribose transferase catalytic activity was confirmed using a series of in vitro assays using [ 32 P]NAD and a recombinant form of the Af1521 protein from the archaebacteria Archaeoglobus fulgidus, possessing an ADP-ribose recognizing module (termed macro domain) know to bind to both free and protein-bound mono and poly-ADP-ribose moieties (29,30) (Fig. 2).…”
Section: Parp12 Is An Interferon-stimulated Gene (Isg) Coding For Amentioning
confidence: 99%
“…1, C and D), indicating that, at least for murine innate cells, PARP12 is a genuine interferon stimulated gene or ISG. Finally, the capacity of PARP12 to express ADP-ribose transferase catalytic activity was confirmed using a series of in vitro assays using [ 32 P]NAD and a recombinant form of the Af1521 protein from the archaebacteria Archaeoglobus fulgidus, possessing an ADP-ribose recognizing module (termed macro domain) know to bind to both free and protein-bound mono and poly-ADP-ribose moieties (29,30) (Fig. 2).…”
Section: Parp12 Is An Interferon-stimulated Gene (Isg) Coding For Amentioning
confidence: 99%
“…Given MACROD2's recently described function in ADP ribosylation (20), and the fact that ER coactivators can have both estrogen dependent and independent mechanisms of mediating tumor growth (27) we sought to examine a broader array of Fig. 2.…”
Section: Macrod2 Overexpression Alters Protein Expression Of Er and Nmentioning
confidence: 99%
“…Studies have demonstrated that MACROD2 deacetylates O-acetyl-ADP ribose, a signaling molecule generated by the deacetylation of acetylated lysine residues in histones and other proteins (19). More recent work demonstrates that MACRO domain containing proteins are involved with mono-ADP ribosylation, and can regulate cell signaling pathways and modify proteins involved with gene transcription (20). Interestingly, MACROD1 (LRP16) has been implicated in modulating ER and androgen receptor (AR) signaling in prior studies (21,22).…”
mentioning
confidence: 99%
“…This indicates that the catalytic activity of ARTD10 is required to recruit GAPDH, but it is not required to induce the formation of these cell bodies. Indeed, as also previously demonstrated [23], catalytically inactive ARTD10 can form these cell bodies. Moreover, their formation is not inhibited by pharmacological inhibition of the catalytic activity of ARTD10, as neither FK866 nor PJ34 affects the formation of these cell bodies.…”
Section: Discussionmentioning
confidence: 59%